Sulfur‐Induced Interface Engineering of Hybrid NiCo2O4@NiMo2S4 Structure for Overall Water Splitting and Flexible Hybrid Energy Storage. Issue 21 (16th September 2019) - Zhao, Depeng; Dai, Meizhen; Liu, Hengqi; Chen, Kunfeng; Zhu, Xiaofei; Xue, Dongfeng; Wu, Xiang; Liu, Jinping
Abstract: To rationally design hybrid structures with unique surface/interface features is very significant due to their multi‐functionalization in energy storage and conversion systems. Generally, single metal oxide as electrode material is still unsatisfactory for its slow electron transportation and inevitable structural collapse. To address these issues, sulfur element‐induced interface‐tailoring hybrid NiCo2 O4 @NiMo2 S4 nanosheet structures with high electrochemical activity are reported through a simple vulcanization process of NiCo2 O4 @NiMoO4 nanosheets. The hybrid NiCo2 O4 @NiMo2 S4 structure presents excellent hydrogen evolution reaction performance with the overpotential of 159 mV at 10 mA cm −2 and low Tafel slope of 53.1 mV dec −1, and overall water splitting abilities with low cell voltage of 1.63 V at 50 mA cm −2 and stability for 13 h. As supercapacitor electrode materials, the hybrid structures exhibit a specific capacitance 519 C g −1 at 1 A g −1, which is higher than that of hybrid NiCo2 O4 @NiMoO4 nanosheets (420 C g −1 ). The asymmetric device delivers an energy density of 30.73 Wh kg −1 at a power density of 374.9 W kg −1 . Abstract : In this work, hybrid‐structured NiCo2 O4 @NiMo2 S4 nanosheets are prepared through a facile solution route. The as‐synthesized products can be used directly as the electrode materials for overall water splitting and hybrid energy storage.